EFFORTS TO INCREASE COMMUNITY WELFARE THROUGH LOCAL POTENTIAL IN KEDUNG SUMBER VILLAGE, BALONGPANGGANG, GRESIK - Widyastuty Anak Agung Sagung Alit; Desma Dwi Rahmadhani (Jurnal Partisipatoris, 2023)
Kedung Sumber village has an area of 227.90 rice farming land with a production of 1595.30 tons. Law no. 6 of 2014 explains that village development is an effort to improve the quality of life for the greatest welfare of the village community by utilizing the potential of the village. Kedung Sumber Village also has several potential natural beauty that can be a natural tourist destination. This study aims to determine the potential of the village and community participation to improve community welfare. This study uses a qualitative descriptive method approach with percentage analysis techniques. Data collection methods are observation, questionnaires, and documentation. The result of the research is that Kedung Sumber village has several potentials that can be developed, namely natural beauty, rice commodities, and non-physical potential in the form of institutions, government, and community enthusiasm in supporting several activities in the village. The most dominant form of community participation in Kedung Sumber village is social participation and the least is skill participation. Efforts to improve community welfare through local potential are increasing community participation in the form of labor participation as the priority and the second priority is developing non-physical potential.